FLIPPED LEARNING IN THE EDUCATIONAL PROCESS: THE ESSENCE, ADVANTAGES, LIMITATIONS (ResearchJet Journal of Analysis and Inventions, 2021)
The article considers the essence of flipped learning and defines the features of the activity of the teacher and students in the process of implementing the inverted learning model. The didactic and technological aspects of the application of this model of teaching at different levels of education are analyzed. The advantages and limitations of using inverted learning in the educational process are formulated.